기무라병으로 오진된, 말초혈액 호산구증가증을 동반한 역형성대세포림프종 - 신윤지; 오지연; 이영석; 민경훈; 이승룡; 심재정; 강경호; 허규영 (Allergy asthma & respiratory disease, 2018)
Hypereosinophilia, defined as an absolute eosinophil count of >1,500/μL, can be caused by a number of allergic, infectious, paraneoplastic and neoplastic disorders. In cases of hypereosinophilia with lymphoid proliferation, pathological confirmation is essential to exclude either myeloid or lymphoid malignancy. A 38-year-old woman with both cervical lymphadenopathies and peripheral blood eosinophilia visited our clinic. She had already performed core biopsy of lymph nodes and diagnosed as Kimura disease at a regional hospital. At the time of our clinic visit, there were no palpable cervical lymph nodes. The blood test showed hypereosinophilia with a high total IgE level. There was no evidence of tissue infiltration of eosinophils except for duodenitis with eosinophilic infiltration. Based on these findings, she was diagnosed as Kimura disease. She treated with high-dose systemic corticosteroid (1 mg/kg) and additional immunosuppressants sequentially used cyclophosphamide and cyclosporine. However, her eosinophilia waxed and waned, and a left inguinal mass was newly found. Excisional biopsy findings showed large atypical lymphoid cells with numerous eosinophilis, and immunohistochemistry showed CD3+, CD20-, CD30+ and anaplastic lymphoma kinase (ALK). The final diagnosis was ALK-negative anaplastic large cell lymphoma. We report a case of anaplastic large cell lymphoma with marked peripheral eosinophilia misdiagnosed as Kimura disease. In the case of hypereosinophilia with lymphadenopathy, it is necessary to differentiate hematologic diseases through immunochemical staining. KCI Citation Count: 0